PENGEMBANGAN FASILITAS DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN DI THE VALLEY BISTRO CAFÉ DAN RESORT HOTEL DAGO BANDUNG - Rizky Mustika Iskandar, - (2010)
This research was carried out in The Valley Bistro Cafe dan Resort Hotel. This research aims to obtain an overview of the development facilities to increase the number of tourist visits in The Valley Resort Hotel. Issues that were examined in this research are existing facility at The Valley Resort Hotel, facilities that need to be developed at The Valley Resort Hotel, and the number of tourist visits before and after the facility was develope. The population in this research are all of tourist who was come to The Valley Resort Hotel and 100 respondents for the sample. This research use descriptive method. I use documentation study, interview, observation, and questionnaire for data collection techniques. Data processing techniques i use qualitative analysis, questionnaire analysis, and SWOT analysis. Based on SWOT analysis unknown that The Valley Resort Hotel have total value 2,25 for internal factor and 2,8 for external factor. This value show for strong internal and external position. This indicates that The Valley Resort Hotel is a good company. But based on kuadran position, The Valley Resort Hotel be in kuadran I position. That means The Valley Resort Hotel have a big strenghts that can take advantage of existing opportunities. So that an proper strategy for this position is aggressive strategy or SO strategy (Strenghts - Opportunities).